PENGARUH INTENSITAS ASET TETAP, TINGKAT HUTANG, KEPEMILIKAN MANAJERIAL DAN PROFITABILITAS TERHADAP TARIF PAJAK EFEKTIF (Faletehan Jurnal Ekonomi dan Bisnis, 2023)
This study aims to analyze the effect of fixed asset intensity, debt level, managerial ownership and profitability on the effective tax rate. This population is food and beverage sub- sector manufacturing companies listed on the Indonesia Stock Exchange in 2017-2021. Sample selection using purposive sampling method. The results of the final sample of 12 companies from a population of 33 companies. The analytical tool used in this study is multiple regression analysis using IBM SPSS Statistic Version 25. The results of this study indicate that the intensity of fixed assets has a significant negative effect on the effective tax rate, the level of debt has a significant positive effect on the effective tax rate, managerial ownership has a significant negative effect on the effective tax rate. Effective tax rates and profitability have a significant negative effect on effective tax rates and profitability.